Application of Skimming Technique to Improve Reading Skills in Finding Main Ideas of Grade V Students of State Elementary School 005 Kotabaru Seberida - Hawa Saputria , livia; Otang Kurniaman; Intan Kartika Sari (Yayasan Thaifah Manshurah Pekanbaru, 2024)
This research aims to improve reading skills in finding the main ideas of fifth grade elementary school students. This research was conducted at SDN 005 Kotabaru Seberida using skimming techniques. The data collection method is carried out by observation and tests. The test was carried out once in each cycle for 22 students and teacher and student observations were carried out twice in each cycle. In cycle I the average score obtained by students was 71.81, this resulted in an increase in reading skills in finding students' main ideas by 31.77% from the initial data. In cycle II the average score obtained by students was 88.18, an increase of 61.67% from the initial data. comparison of the completeness of individual students' learning results, initially only 13.63% or 3 students passed out of 100% or 22 students in the class. After taking action in the learning process by applying the skimming technique, there was an increase, namely in cycle I there were 10 students who completed or 45.45% and 12 students or 54.54% who did not complete. Finally, in cycle II there were 20 students or 90.90% of students who completed and 2 people or 9.09% of students who did not complete. It can be concluded that by applying skimming techniques to reading skills in finding the main idea, students can increase the grades they get